Distinct activation mechanisms trigger the trypanocidal activity of DNA damaging prodrugs. Issue 2 (31st August 2017) - Meredith, Emma Louise; Kumar, Ambika; Konno, Aya; Szular, Joanna; Alsford, Sam; Seifert, Karin; Horn, David; Wilkinson, Shane R.
Summary: Quinone‐based compounds have been exploited to treat infectious diseases and cancer, with such chemicals often functioning as inhibitors of key metabolic pathways or as prodrugs. Here, we screened an aziridinyl 1, 4‐benzoquinone (ABQ) library against the causative agents of trypanosomiasis, and cutaneous leishmaniasis, identifying several potent structures that exhibited EC50 values of <100 nM. However, these compounds also displayed significant toxicity towards mammalian cells indicating that they are not suitable therapies for systemic infections. Using anti‐ T . brucei ABQs as chemical probes, we demonstrated that these exhibit different trypanocidal modes of action. Many functioned as type I nitroreductase (TbNTR) or cytochrome P450 reductase (TbCPR) dependent prodrugs that, following activation, generate metabolites which promote DNA damage, specifically interstrand crosslinks (ICLs). Trypanosomes lacking TbSNM1, a nuclease that specifically repairs ICLs, are hypersensitive to most ABQ prodrugs, a phenotype exacerbated in cells also engineered to express elevated levels of TbNTR or TbCPR. In contrast, ABQs that contain substituent groups on the biologically active aziridine do not function as TbNTR or TbCPR‐activated prodrugs and do not promote DNA damage. By unravelling how ABQs mediate their activities, features that facilitate the desired anti‐parasitic growth inhibitory effects could be incorporated into new, safer compounds targeting these neglected tropical diseases. Abstract : Trypanocidal mechanism of aziridinyl benzoquinones. Reduction of quinones to hydroquinones occurs: indirectly by a series of 1 e – reductions (e.g., by cytochrome P450 reductases (CPR)), or directly by a 2 e – reduction (e.g., by type I nitroreductases (NTR)). Hydroquinone formation facilitates aziridine protonation, promoting nucleophilic attack, e.g., by DNA, and leads to alkylation of the target. As the aziridinyl benzoquinones tested here contain multiple aziridinyls, they can bind to the complementary DNA strands generating interstrand crosslinks.